Utdelning och kvinnors roll i företagsstyrelser - Ljunggren,Julia; Ljungdahl,Ida; Juväng,Maja (2025)
This study aims to investigate the relationship between board gender diversity and dividend payouts, using data from 70 non-financial companies in Denmark, Finland and Sweden from 2014 to 2023. Using a dynamic fixed effects regression model with one and two lags, we analyze whether board gender diversity significantly affects dividend payout. We collect board- and firm-specific data from Eikon for 70 non-financial public companies. The study is based on the Principal-Agent theory, which explores the relationship between shareholders and company management. Additionally, the Critical Mass theory is applied, emphasizing how the presence of a certain number of women on boards may influence the decision-making process. This study finds no significant effect of board gender diversity on dividend payout. The results remain consistent across multiple robustness tests, including the use of an alternative measure of dividend payout and controlling for the Critical mass theory.
Keywords: Styrelse; Könsmångfald; Kvinnliga styrelseledamöter; Utdelningsnivå; Utdelningspolicy